Identification of molecular markers linked to Fusarium ear rot genes in maize plants Zea mays L - M. M. Abdel-Rahman; S. R. Bayoumi; M. N. Barakat (Biotechnology & Biotechnological Equipment, 2016)
Two maize populations (GE440 × Sd7 and NC300 × Gm1002) were used in this study. Molecular markers like simple sequence repeat (SSR) and sequence-tagged site (STS) were used to identify resistance genes linked to Fusarium ear rot (Fusarium verticillioides). Also, quantitative trait locus (QTL) mapping was used to detect resistance genes on maize chromosomes. The co-dominant microsatellite markers (bnlg1063, umc2082, bnlg1621, umc2013, bnlg1740, umc2059 and SSR85) and STS (STS06) were amplified polymorphic bands and candidate markers linked to Fusarium ear rot resistance genes in maize. Seven QTLs were identified ranging from 2 to 7 for each trait. QTLs were distributed on two chromosomes and associated with grain yield/main ear and 100 kernel weight. The present study indicated that microsatellite and STS primers might be useful for developing improved cultivars.